Perception of climate change effects on forest-dependent rural livelihoods in Ondo State, Nigeria (2016)
Rural population is the highest in developing countries with pathetic living condition and lack of resources to cope with ecological perturbations apart from not having social opportunities to cushion the impacts of extreme events. This paper reports the impacts of climate change on the livelihoods of forest dependent rural populations in Ondo State, a forest rich southwestern part of Nigeria, with the view to identifying possible adaptation strategies. Stratified multistage simple random sampling was used in selecting respondents for the study. The state was stratified into Local Government Areas (LGAs) and Four (4): Odigbo, Akure North, Owo and Idanre were randomly selected. In each of the LGAs selected, one forest reserve each (Oluwa, Ala, Owo and Idanre, respectively) was selected. Three rural communities surrounding each of the forest reserve were then selected as study site while 30 households were randomly selected for interview. Primary data were collected from the selected households in the selected communities using a set of structured and open-ended questionnaire. Data were analysed using descriptive and inferential statistics at α0.05. Generally, more (62.2%) respondents noticed changes in rainfall pattern, which led to flooding in 2014, while 37.2% noticed increase temperature, which led to the drought of 2007. On availability of forest resources, majority (78.6%) of the respondents noticed changes in the availability of Mansonia, while 12.0%,8.0%, 5.5% and 4.7% attested to changes in the availability of Terminalia superba, Gmelina, Tectona grandis (Teak) and Obeche, respectively. Similarly, 78.0% of the respondents noticed changes in availability of firewood, while changes in the availability of seeds, fruits and mushrooms were attested to by 15.0%, 4.7%, and 1.4% of the respondents, respectively. Identified impacts of climate change by the respondents included among others reduction in agricultural production, flooding, increased livestock death and shortage of food. Suggested mechanisms for coping with climate change adversities included changing of the planting date, practice of agroforestry, planting of trees and early harvesting regime. Climate change was found to impact agricultural and rural land use in the study area. Therefore, the adoption of agroforestry practices as rural land use is recommended in Ondo State as an adaptation measure against climate change.